(untitled) (Research, Society and Development, 2022)
School has been considered an important space for the development of healthier eating habits. The agroecological school gardens are opportunities to enrich school meals with the inclusion of natural products, favoring the supplementation of vitamin and mineral needs, and promoting changes in eating habits of students and the school community. The project was developed from March 2020 to March 2022 in the Walnyza Borborema Cunha Lima Municipal Daycare Center, located in the municipality of Campina Grande, PB, during the Covid-19 pandemic, as a coping strategy, aiming to provide food to families with children enrolled in the daycare center and who were in a situation of economic and social vulnerability. The delivery of the food kits contributes to improving the food and nutritional security of the families assisted. The agro-ecological management adopted contributes to the maintenance of soil nutrition and fertility, plant health, and plant production in the desired quality and quantity. The insertion of the community in the daily school routine enables educational actions. The experience of children up to 5 years old in the school garden contributes to the construction of healthy eating habits and reduction of food waste, especially vegetables. The successful experience achieved in the Walnyza Borborema Cunha Lima Municipal Daycare serves as a model to be reproduced by other daycare centers and schools, integrating the community into the school environment through social and environmental actions that promote sustainable development of the entire community involved.